anonymous
  • anonymous
how do you write the equation of a hyperbola .... 4x^2 -y^2+16x+6y-3=0 ....... in standard form?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
nikvist
  • nikvist
\[4x^2 -y^2+16x+6y-3=0\]\[4x^2 +16x-y^2+6y=3\]\[4x^2 +16x+16-y^2+6y-9=10\]\[4(x+2)^2-(y-3)^2=10\]\[\frac{(x+2)^2}{5/2}-\frac{(y-3)^2}{10}=1\]
nikvist
  • nikvist
you made mistake 6y, not 16y
Hero
  • Hero
You have \[4x^2 - y^2 + 16x + 6y - 3 = 0\] Re-arrange the terms so that you have \(x^2 + 16x\) on the left side as follows: \[4x^2 + 16x = y^2 - 6y + 3\]\[x^2 + 4x = \frac{y^2 - 6y + 3}{4}\] Because the left side is in the form \(x^2 + bx\) add \((b/2)^2\) to both sides. In this case \((b/2)^2 = 4\) since \((4/2)^2 = (2)^2 = 4\):\[x^2 + 4x + 4 = \frac{y^2 - 6y + 3}{4} + 4\]On the left side, re-write the completed square as a perfect square binomial. On, the right side, Re-write 4 as \(\frac{16}{4}\), then combine fractions:\[(x + 2)^2 = \frac{y^2 - 6y + 3}{4} + \frac{16}{4}\]\[(x + 2)^2 = \frac{y^2 - 6y + 3 + 16}{4} \]\[(x + 2)^2 = \frac{y^2 - 6y + 19}{4} \]Multiply both sides by 4, then subtract 19 from both sides leaving \(y^2 - 6y\) on the right side:\[4(x + 2)^2 -19 = y^2 - 6y\]Again, we have the form \(y^2 + by\) so add \((b/2)^2\) to both sides. In this case, b = -6 so \((-6/2)^2 = (-3)^2 = 9\): \[4(x + 2)^2 -19 + 9= y^2 - 6y + 9\] Re-write the right side as a binomial square: \[4(x+2)^2 - 10 = (y - 3)^2\] Continue re-arranging until you reach the desired form: \[4(x+2)^2 - (y-3)^2 = 10\] \[\frac{4(x+2)^2 - (y-3)^2}{10} = 1\] \[\frac{4(x+2)^2}{10} -\frac{ (y-3)^2}{10} = 1\] \[\frac{2(x+2)^2}{5} -\frac{ (y-3)^2}{10} = 1\]

Looking for something else?

Not the answer you are looking for? Search for more explanations.